Community status of giant clam (Tridacnidae) on Bira of Seribu Islands, Indonesia - RATNA KOMALA; DIANA VIVANTI SIGIT; EKA PUTRI AZRA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Komala R, Sigit DV, Azrai EP. 2025. Community status of giant clam (Tridacnidae) on Bira of Seribu Islands, Indonesia. Biodiversitas 26: 1891-1897. The Tridacnidae family, commonly referred to as giant clams, has a comparatively high ecological and commercial potential but is vulnerable to environmental shifts and human activities. The study aims to identify species of Tridacnidae, ascertain their abundance, diversity, and dominance, and examine the correlation between environmental factors and the population abundance of giant clams on Bira of Seribu Islands, Indonesia. The location of the observation is determined purposefully based on the coral reef existence. Data collection was carried out using the line Transect method, which involves measuring 10 transects over 100 meters from the shore to the reef edge. The Underwater Photo Transect (UPT) sample collection technique was employed at a depth of between 3 and 4.5 meters. The Mantel test was used to examine the relationship between environmental parameters and the abundance of giant clams. In contrast, the abundance, biodiversity, and dominance index formulas were used to interpret the data. The result identified three species of giant clams from the genera Tridacna and Hippopus, with T. maxima showing the highest abundance, followed by T. gigas and H. hippopus. The diversity encompassed the low to middle criteria with low criteria dominance. Environmental parameters remained within a range favorable for the growth of giant clams, but there is no significant correlation between the environmental parameters with the abundance of Tridacnidae.